2003
DOI: 10.1016/s0304-3959(02)00301-9
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in awake rats reduces formalin-induced nociceptive behaviour and fos-immunoreactivity in trigeminal nucleus caudalis

Abstract: Besides its well-established efficacy in epilepsy, vagus nerve stimulation (VNS) may be of potential interest in pain treatment. It has, however, not yet been assessed in animal pain models with the devices and stimulation protocols used in humans. We have therefore studied in awake rats the effects of left cervical VNS on trigeminal nociception using an implantable electrode and stimulator (NCP-Cyberonics). VNS was applied for 24h at 2 mA intensity, 20 Hz frequency, 0.5 ms pulse width and a duty cycle of 20s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 89 publications
1
29
0
Order By: Relevance
“…We recorded with microelectrodes the neuronal activity of the trigeminal nucleus caudalis (NC) in anaesthetized rats. This nucleus was elected because clinical (Green et al 2002;Morita and Hosobuchi 1992;Rosenkopf 1989), behavioral (Bohotin et al 2003;Duale et al 1996;Luccarini et al 1998;Rosenfeld et al 1983), anatomical (Clements et al 1991;Coimbra and Coimbra 1994;Strassman and Vos 1993;Voisin et al 2002), immunohistochemical (Strassman and Vos 1993;Bereiter et al 1994;Lu et al 1993;Meng and Bereiter 1996;Oakden and Boissonade 1998), and electrophysiological (Amano et al 1984;Carstens et al 1998;Chiang et al 1991;Dallel et al 1998;Hu et al 1981;Tsai et al 1999) evidence suggest that it is the most important site for relay of orofacial nociceptive information.…”
Section: Striatal Stimulationmentioning
confidence: 99%
“…We recorded with microelectrodes the neuronal activity of the trigeminal nucleus caudalis (NC) in anaesthetized rats. This nucleus was elected because clinical (Green et al 2002;Morita and Hosobuchi 1992;Rosenkopf 1989), behavioral (Bohotin et al 2003;Duale et al 1996;Luccarini et al 1998;Rosenfeld et al 1983), anatomical (Clements et al 1991;Coimbra and Coimbra 1994;Strassman and Vos 1993;Voisin et al 2002), immunohistochemical (Strassman and Vos 1993;Bereiter et al 1994;Lu et al 1993;Meng and Bereiter 1996;Oakden and Boissonade 1998), and electrophysiological (Amano et al 1984;Carstens et al 1998;Chiang et al 1991;Dallel et al 1998;Hu et al 1981;Tsai et al 1999) evidence suggest that it is the most important site for relay of orofacial nociceptive information.…”
Section: Striatal Stimulationmentioning
confidence: 99%
“…Continuous vagal nerve stimulation (VNS) for 24 hours in awake rats produced significant antinociceptive effects in a model of trigeminal pain [64]. This showed that VNS stimulation significantly inhibits activation of second-order nociceptors in the TNC and pain-related behavior on the side of the facial nociceptive stimulus during the early and late phase.…”
Section: Autonomic-trigeminocervical Connectionsmentioning
confidence: 99%
“…The analgesic effect of the vagal afferent stimulation has been reported in numerous behavioral pain tests in laboratory animals. For instance, the VNS-induced inhibition of the nociceptive digastric reflex induced by intense tooth-pulp stimulation (Maixner et al, 1991;Bossut et al, 1992), reduction of the cumulative duration of rubbing and scratching the injection site in the orofacial formalin test (Bohotin et al, 2003b), and latency increase of the tail-flick or the hind paw withdrawal response to noxious heat (Ren et al, 1989;Aicher et al, 1991;Thurston and Randich, 1991;Bohotin et al, 2003a) were reported. In epileptic patients treated with VNS, an increase in mechanical pain threshold was noted (Kirchner et al, 2000(Kirchner et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%